Pyrene Functionalized Highly Reduced Graphene Oxide-palladium Nanocomposite: A Novel Catalyst for the Mizoroki-Heck Reaction in Water - Khan, Mujeeb; Ashraf, Muhammad; Shaik, Mohammed Rafi; Adil, Syed Farooq; Islam, Mohammad Shahidul; Kuniyil, Mufsir; Khan, Merajuddin; Hatshan, Mohammad Rafe; Alshammari, Riyadh H.; Siddiqui, Mohammed Rafiq H.; Tahir, Muhammad Nawaz (Frontiers in Chemistry, 2022)
The formation of a C-C bond through Mizoroki-Heck cross-coupling reactions in water with efficient heterogeneous catalysts is a challenging task. In this current study, a highly reduced graphene oxide (HRG) immobilized palladium (Pd) nanoparticle based catalyst (HRG-Py-Pd) is used to catalyze Mizoroki-Heck cross-coupling reactions in water. During the preparation of the catalyst, amino pyrene is used as a smart functionalizing ligand, which offered chemically specific binding sites for the effective and homogeneous nucleation of Pd NPs on the surface of HRG, which significantly enhanced the physical stability and dispersibility of the resulting catalyst in an aqueous medium. Microscopic analysis of the catalyst revealed a uniform distribution of ultrafine Pd NPs on a solid support. The catalytic properties of HRG-Py-Pd are tested towards the Mizoroki-Heck cross-coupling reactions of various aryl halides with acrylic acid in an aqueous medium. Furthermore, the catalytic efficacy of HRG-Py-Pd is also compared with its non-functionalized counterparts such as HRG-Pd and pristine Pd NPs (Pd-NPs). Using the HRG-Py-Pd nanocatalyst, the highest conversion of 99% is achieved in the coupling reaction of 4-bromoanisol and acrylic acid in an aqueous solution in a relatively short period of time (3 h), with less quantity of catalyst (3 mg). Comparatively, pristine Pd NPs delivered lower conversion (∼92%) for the same reaction required a long reaction time and a large amount of catalyst (5.3 mg). Indeed, the conversion of the reaction further decreased to just 40% when 3 mg of Pd-NPs was used which was sufficient to produce 99% conversion in the case of HRG-Py-Pd. On the other hand, HRG-Pd did not deliver any conversion and was ineffective even after using a high amount of catalyst and a longer reaction time. The inability of the HRG-Pd to promote coupling reactions can be attributed to the agglomeration of Pd NPs which reduced the dispersion quality of the catalyst in water. Therefore, the high aqueous stability of HRG-Py-Pd due to smart functionalization can be utilized to perform other organic transformations in water which was otherwise not possible.